Package graphic design development: An experimental test of the validity of focus groups as a consumer research input. Issue 9 (4th September 2017) - Hamlin, Robert P.; Gin, Michael; Nyhof, Fiona; Bogue, Joe
Abstract : Purpose: The purpose of this paper is to establish whether consumer focus groups can generate reliable data when used as a consumer research input to copy/graphic design development for retail food packaging. Design/methodology/approach: Six focus groups of six consumers each ( n =36) were used to assess four concept designs for a manuka honey cordial product. The focus groups were used to rank the design concepts and to generate specific consumer-driven recommendations to develop/improve each of the designs. A new version of each design was then developed using these recommendations. The eight designs (four original and four improved) were tested together, using a quantitative field experiment at a supermarket in the area from which the focus group sample was drawn. Findings: The results showed that the focus group rankings of the four original designs were largely predictive of the outcomes of the field trial. The improved designs also consistently outperformed their original equivalents in the field trials. Very large improvements were recorded with respect to the weaker original designs. Research limitations/implications: The research only studied a single product type. However, the results demonstrate that focus group outcomes can be extended onto larger populations if the focus group sample is large enough. Practical implications: These results support the use of consumer focus groups as a research input to package graphic design development. Originality/value: Focus groups are used regularly in research where the applicability of their results to larger populations is assumed. This is the first research to formally test that assumption.